The Impact of Falling Oil Prices: Is Latin America Part of Global Oil Supply Adjustment? - Palacios, Luisa (2015)
International oil prices have declined by 40% recently. Some of the region’s oil producers have been better than others at adjusting to this reality. In more market- oriented countries like Colombia and Mexico, the collapse of oil prices has not translated into a full-blown crisis thanks to the flexibility of their policy frameworks. In these countries, their floating foreign exchange rate regimes are doing the work of helping their economies deal with the external and fiscal adjustment that such collapse in oil prices entails. But in those countries like Venezuela that are unable or unwilling to adjust, the oil price collapse is significantly deteriorating their dollar liquidity situation and leading to a serious macroeconomic crisis.